Adrenocortical Tumors and Pheochromocytoma/Paraganglioma Initially Mistaken as Neuroblastoma—Experiences From the GPOH-MET Registry - Kuhlen, Michaela; Pamporaki, Christina; Kunstreich, Marina; Wudy, Stefan A.; Hartmann, Michaela F.; Peitzsch, Mirko; Vokuhl, Christian; Seitz, Guido; Kreissl, Michael C.; Simon, Thorsten; Hero, Barbara; Frühwald, Michael C.; et al. (Frontiers in Endocrinology, 2022)
In children and adolescents, neuroblastoma (NBL), pheochromocytoma/paraganglioma (PCC/PGL) and adrenocortical tumors (ACT) can arise from the adrenal gland. It may be difficult to distinguish between these three entities. Precise discrimination, however, is of crucial importance for initial management. Biopsy in ACT or PCC is potentially harmful and should be avoided whenever possible. We herein report data on 10 children and adolescents with ACT and 5 with PPGL, previously mistaken as NBL. Two (2/9, missing data in one patient) patients with final diagnosis of ACT clearly presented with obvious clinical signs and symptoms of steroid hormone excess while 7 patients did not. Blood analysis determined increased levels of steroid hormones in one additional patient; however, steroid hormone urine analysis was not performed in any patient. Two (2/10) patients underwent tumor biopsy, in 2 additional patients tumor rupture occurred intraoperatively. In 6 of 10 patients, ACT diagnosis was only established by reference pediatric pathology review. Four of five patients with final diagnosis of PCC/PGL presented with clinical signs and symptoms of catecholamine excess. Urine analysis determined at least suspicious findings in 2 patients, while urine analysis was not done in 3 patients. Measurements of plasma metanephrines were not performed in any patient. Adrenergic blockage drugs were not used in any patient prior to/during surgery. In 4 patients, PCC/PGL diagnosis was established by a local pathologist, in one patient diagnosis was revised to PGL by a pediatric reference pathologist. Genetic testing indicated variants of PCC/PGL susceptibility genes in 3 patients, while data are missing in 2 patients. The differential diagnosis of adrenal neoplasias in children and adolescents may be challenging. Comprehensive biochemical testing, complete tumor resection, and reference pathology are vital to prevent misdiagnosis and, thus, poor outcome in children and adolescents with ACT or PCC/PGL.